Polarization, Foreign Military Intervention, and Civil Conflict - Abu Bader, Suleiman; Ianchovichina, Elena (World Bank, Washington, DC, 2017)
In a behavioral model of civil conflict, foreign military intervention alters the resources available to warring groups and their probability of winning. The model highlights the importance of distributional measures along with the modifying effect of the intervention for conflict incidence. The paper confirms empirically the finding in the literature that ethnic polarization is a robust predictor of civil war, but it also finds evidence that religious polarization is positively and significantly associated with civil conflict in the presence of foreign military intervention of non-humanitarian and non-neutral nature. Such external interventions exacerbate religious polarization, leading to high-intensity conflicts in the Middle East and North Africa region, but not in the rest of the world. These results suggest that, unlike in the rest of the world, where civil conflicts are mostly about a public prize linked to ethnic polarization, in the Middle East and North Africa they are mostly about a sectarian-related public prize. The results are robust to allowing different definitions of conflict, model specifications, and data time spans, and to controlling for other types of foreign military interventions.